PENGARUH METODE INQUIRI TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIK SISWA SMAN 1 MANDE KABUPATEN CIANJUR - ABDUL JALALUDIN (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2021)
This research is an experimental study that focuses on increasing the mathematical creative thinking skills of high school students by applying the inquiry learning method. The problem behind this research is the lack of familiarity with learning using methods with a focus on learning on students as a way to get a more meaningful learning experience based on students' creative thinking skills that are different for each student. The aims of this study are: 1) To determine the effect of the inquiry learning method on students' mathematical creative thinking skills. 2) to find out the comparison of increasing students' mathematical creative thinking skills using the inquiry learning method with conventional learning; 3) to determine students' attitudes towards learning the inquiry method. This study used the experimental design method "design control group pretest-posttest", which was carried out in class X SMA Negeri 1 Mande Cianjur which consisted of 5 study groups with the experimental class sample being class X-4 and the control class sample being class X-3. The indicators of mathematical creative thinking skills measured in this study are: 1) the ability to replace (Substitute), combine (Combine), adjust (Adapt), modify (Magnify/Modify), for other uses (Put to other use), Delete (Eliminate). ) and rearrange (Rearrange/Reverse) from existing capabilities; 2) the ability to rearrange existing abilities/reverse with flexibility (trying new things), authenticity (answering their own way) and outlining (developing ideas) in understanding something. The results showed that: 1) the inquiry learning method had an influence on students' mathematical creative thinking abilities; 2) the inquiry learning method has an improvement in students' mathematical creative thinking which is better than the conventional method; 3) students have a positive attitude towards the inquiry learning method. ABSTRAK Penelitian ini merupakan penelitian eksperimen yang difokuskan pada peningkatan kemampuan berpikir kreatif matematik siswa SMA dengan menerapkan metode pembelajaran inquiri. Masalah yang melatar belakangi penelitian ini adalah kurang dibiasakanya pembelajaran menggunakan metode dengan pemusatan pembelajaran pada siswa sebagai cara untuk memperoleh pengalaman belajar yang lebih bermakna dengan dilandasi kemampuan berpikir kreatif siswa berbeda pada setiap siswa. Tujuan penelitian ini adalah : 1) Untuk mengetahui pengaruh metode pembelajaran  inquiri terhadap kemampuan berpikir kreatif matematik siswa. 2) untuk  mengetahui perbandingan peningkatan kemampuan berpikir kreatif matematik siswa menggunakan metode pembelajaran inquiri dengan pembelajaran konvensional; 3) untuk mengetahui sikap siswa terhadap pembelajaran metode inquiri. Penelitian ini menggunakan metode eksperimen desain “desain countrol group pretes-postes”, yang dilakukan di kelas X SMA Negeri 1 Mande Cianjur yang berjumlah 5 rombongan belajar dengan sampel kelas eksperimen adalah kelas X-4 dan sampel kelas kontrol adalah kelas X-3. Indikator kemampuan berpikir kreatif matematik yang diukur dalam penelitian ini adalah: 1) kemampuan mengganti (Substitute), mengkombinasi (Combine), menyesuaikan (Adapt), memodifikasi (Magnify/Modify), untuk kegunaan lain (Put to other use), Menghapus (Eliminate) dan menyusun kembali (Rearrange/Reverse) dari kemampuan yang telah ada; 2) kemampuan menyusun kembali kemampuan/membalik  yang telah ada dengan keluwesan (mencoba hal baru), keaslian (menjawab cara sendiri) dan menguraikan  (mengembangkan ide) dalam  memahami suatu hal. Hasil penelitian menunjukkan bahwa: 1) metode pembelajaran inquiri memiliki pengaruh terhadap kemampuan berpikir kreatif matematik siswa; 2) metode pembelajaran inquiri memiliki peningkatan berpikir kreatif matematik siswa yang lebih baik dari pada metode konvensional; 3) siswa memiliki sikap positif terhadap metode pembelajaran inquiri.